54.4k views
1 vote
Factor the GCF: -6x^4y^5 - 15x^3y^2 + 9x^2y^3

User Avn
by
5.8k points

1 Answer

3 votes
-6x^4y^5 - 15x^3y^2 + 9x^2y^3

-6x^4y^5 = -2, 3, x, x, x, x, y, y, y, y, y
15x^3y^2 = -5, 3 x, x, x, y, y
9x^2y^3 = 3, 3 x, x, y, y, y

Each group has a 3 in common and each group has 2 x in common and each group has 2 y in common so the GCF = -3x^2y^2

Divide that out and we get

(-6x^4y^5 - 15x^3y^2 + 9x^2y^3)/(-3x^2y^2) =

2x^2y^3 + 5x - 3y

-3x^2y^2(2x^2y^3 + 5x - 3y)

User Sudheeshcm
by
5.3k points